2022
DOI: 10.3390/antiox11091713
|View full text |Cite
|
Sign up to set email alerts
|

ROS Suppression by Egg White Hydrolysate in DOCA-Salt Rats—An Alternative Tool against Vascular Dysfunction in Severe Hypertension

Abstract: This study aimed to evaluate the potential for lowering blood pressure and beneficial effects on mesenteric resistance arteries (MRA) and conductance vessels (aorta) produced by dietary supplementation of an egg white hydrolysate (EWH) in rats with severe hypertension induced by deoxycorticosterone plus salt treatment (DOCA-salt), as well as the underlying mechanisms involved. The DOCA-salt model presented higher blood pressure, which was significantly reduced by EWH. The impaired acetylcholine-induced relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Moreover, it is known that specific amino acids and their position in the sequence are essential for bioactivity (34,35) . The antihypertensive effect produced after EWH administration in the DOCA-salt model was a 32 % reduction in SBP, corroborating a previous report using this hydrolysate (20) . Other bioactive compounds derived from foods have also demonstrated antihypertensive effects in hypertensive experimental models, specifically in DOCA-salt hypertensive animals.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, it is known that specific amino acids and their position in the sequence are essential for bioactivity (34,35) . The antihypertensive effect produced after EWH administration in the DOCA-salt model was a 32 % reduction in SBP, corroborating a previous report using this hydrolysate (20) . Other bioactive compounds derived from foods have also demonstrated antihypertensive effects in hypertensive experimental models, specifically in DOCA-salt hypertensive animals.…”
Section: Discussionsupporting
confidence: 91%
“…Bioactive compounds from animal sources, particularly bioactive peptides, have been extensively studied. In this context, an egg white hydrolysate (EWH) produced by treatment with pepsin for 8 hours has demonstrated antioxidant, anti-inflammatory and/or antihypertensive properties in several experimental models such as Zucker obesity (17) , spontaneously hypertensive rat (18) , metabolic syndrome (19) and deoxycorticosterone acetate (DOCA)-salt hypertension (20) related to the action of bioactive peptides which are included on EWH.…”
Section: Highlightsmentioning
confidence: 99%
“…And Aleksandra et al (2014) reported that EYPs exerted a strong ACE inhibitory activity (IC 50 of 9.4 µg/mL), which has been attributed mainly to the glutamic acid residue at the C-terminal positions [95]. Moreover, it has been found that oxidative stress is related to vascular damage in hypertensive patients, due to the degradation of excessive reactive oxygen species (ROS) and nitric oxide (NO) [124]. Zhang et al (2020) reported that LAPYK, identified from EWPPs, had an ABTS scavenging IC 50 of 5.29 ± 0.24 µM and ORAC of 1.50 ± 0.04 µM TE/µM, and found that LAPYK has potential to exhibit antihypertensive activity [118].…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…We used this model to demonstrate that it induces severe hypertension and impacts blood volume; thus, it is useful for studies on resistant hypertension (Lee et al 2015;Abreu et al 2022). It is widely known that salt sensitivity plays a role in the onset of essential hypertension in humans (Grillo et al 2019).…”
Section: Introductionmentioning
confidence: 99%